Meningkatkan Pembelajaran Hockey Melalui Permainan 4 Gawang Kecil (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this result the study learning of hockey games through the 4 Small Wicket Game in Grade VIII 3 students of Smp Muhammadiyah 4 Semarang. In this case the right is 4 semarang. research method. In practice consists of two cycles. Based on the results of the research, it showed the percentage of passing students study result in the first cycle, students who got pass score are 58.33% (21 students) and who did not pass are 41.66% (15 students). In the second cycle students who got pass score are 88.88% (34 students) and students who did not pass are 11.11% (4 students). It indicates an increase completeness of student study result is 30.55%.Based on the research’s result, it can be concluded that the use of 4 Small Wicket Game in Grade VIII 3 students is right to improve the study result of grade VIII 3 students of SMP Muhammadiyah 4 Semarang in learning hockey